2023
DOI: 10.3390/biomedicines11051436
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Based Hydrogel Micropatches with Human Adipose-Derived Stem Cells: A Promising Therapeutic Approach for Neuropathic Pain Relief

Abstract: This study explores the therapeutic efficacy of heparin-based hydrogel micropatches containing human adipose-derived stem cells (hASCs) in treating neuropathic pain caused by nerve damage. Our results showed that hASCs exhibited neuroregenerative and pain-relieving effects when used with heparin-based hydrogel micropatches in the neuropathic pain animal model. The use of this combination also produced enhanced cell viability and nerve regeneration. We conducted various neurological behavioral tests, dynamic pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The heparin-based hydrogel micropatches can promote the proliferation and maintain the stemness of hAD-MSCs in vitro. Furthermore, they can improve the survival rate and retention rate of hAD-MSCs in injured nerve tissue, and enhance the therapeutic effect of hAD-MSCs in nerve repair and pain relief [ 79 ].…”
Section: Optimization Strategies For Msc-based Analgesia Therapymentioning
confidence: 99%
“…The heparin-based hydrogel micropatches can promote the proliferation and maintain the stemness of hAD-MSCs in vitro. Furthermore, they can improve the survival rate and retention rate of hAD-MSCs in injured nerve tissue, and enhance the therapeutic effect of hAD-MSCs in nerve repair and pain relief [ 79 ].…”
Section: Optimization Strategies For Msc-based Analgesia Therapymentioning
confidence: 99%
“…We have previously reported that the paracrine effect of transplanted cells causes SCI recovery. [35][36][37][38] Although the transplanted cells do not survive for up to eight weeks, the embedded SCs secrete cytokines, exosomes, and paracrine factors, while the ECs secrete neurotransmitters that induce axonal regeneration. 39,40 In addition, we have demonstrated that the hydrogel is an excellent material for the treatment of neurodegeneration and results in behavioral improvement after SCI.…”
Section: Biomaterials Science Papermentioning
confidence: 99%